2019
DOI: 10.1002/fsn3.868
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid alleviates obesity and modulates gut microbiota in high‐fat‐fed mice

Abstract: To evaluate the anti‐obesity effects of chlorogenic acid (CGA), the mice were fed a high‐fat diet (HFD) upon chlorogenic acid treatment for 6 weeks. The results showed administration of chlorogenic acid (150 mg per kg per day) remarkably promoted body loss, reduced lipid levels in plasma and altered mRNA expression of lipogenesis and lipolysis related genes in adipose tissue. Moreover, chlorogenic acid also reversed the HFD‐induced gut microbiota dysbiosis, including significantly inhibiting the growth of Desu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 48 publications
(35 reference statements)
8
93
2
2
Order By: Relevance
“…Previous studies have shown that A. keiskei chalcone extract prevents adiposity in mice fed a high‐fat diet (HFD) . In addition, flavonoids, coumarins, and phenolic acids in A. keiskei also have anti‐obesity effects . The ability of phytochemical‐rich foods to prevent obesity and metabolic diseases via gut microbiota modulation has been extensively reported .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that A. keiskei chalcone extract prevents adiposity in mice fed a high‐fat diet (HFD) . In addition, flavonoids, coumarins, and phenolic acids in A. keiskei also have anti‐obesity effects . The ability of phytochemical‐rich foods to prevent obesity and metabolic diseases via gut microbiota modulation has been extensively reported .…”
Section: Introductionmentioning
confidence: 99%
“…Also, in rats treated with chlorogenic acid-polyphenols (rich in green coffee bean), the concentration of beneficial bacteria such as Bacteroides, Bifidobacterium, and Lactobacillus spp. was significantly increased, while the composition of Ruminococcaceae, Desulfovibrionaceae, Lachnospiraceae, and Erysipelotrichaceae decreased with the experimental treatment [51]. Moreover, phenolic compounds extracted from Allium sativum juice decrease the growth of pathogenic bacteria such as Staphylococcus epidermidis and Klebsiella pneumoniae [52].…”
Section: Phenolic Compoundsmentioning
confidence: 96%
“…CGA was shown to have potent antimicrobial activity by binding and permeabilizing the bacterial cell membrane . In ICR male mice (29–31 g) with HFD‐induced dysbiosis, oral CGA (150 mg d −1 for 6 weeks) inhibited the growth of Desulfovibrionaceae, Ruminococcaceae, Lachnospiraceae and Erysipelotrichaceae, and improved the growth of Bacteroidaceae and Lactobacillaceae, therefore reversing the HFD‐induced gut microbiota dysbiosis . In another study using male Kunming mice (20–30 g) with Pb‐induced cognitive impairments and hepatic and renal toxicity, oral CGA (30 mg kg −1 d −1 for 8 weeks) had a remarkable reversion effect of the Pb‐induced dysbiosis by increasing Helicobacter and decreasing Lachnospiraceae ratios …”
Section: Hca Interactions With the Gut Microbiotamentioning
confidence: 99%